EFFECT OF AGROCLIMATE ON SEED AND SEEDLING TRAITS OF TREE BEAN (Parkia timoriana (DC) Merr.) IN NORTH EAST INDIA - Uttam Thangjam; Uttam Kumar Sahoo; Pentile Thong (Indonesian Journal of Forestry Research, 2019)
Parkia timoriana (DC) Merr (popularly known as tree bean) is a leguminous tree species found distributed in several South-East Asian countries like Indonesia, Japan, Malayasia, Phillipines, Thailand, Vietname including the mid and foothills of eastern Himalayas. We identified the seed source of this species and grouped them into different agro climatic zones based on moisture index and precipitation. The resultant agroclimatic zones were analysed for significant influences on quantitative traits of seeds and seedlings of P. timoriana and their contribution to germination and growth. Analysis of variance showed significant variation (p humid > subhumid > perhumid. We recommend tree breeders to chose of P. timotiana from arid zone (MI = -20 to -60) for establishing seed orchard for optimum yield. Further, ARCGIS interpolation tool could be of use for predicting better seed source of this species in plantation programmes.